2013
DOI: 10.1371/journal.pone.0064776
|View full text |Cite
|
Sign up to set email alerts
|

Collective-Goal Ascription Increases Cooperation in Humans

Abstract: BackgroundCooperation is necessary in many types of human joint activity and relations. Evidence suggests that cooperation has direct and indirect benefits for the cooperators. Given how beneficial cooperation is overall, it seems relevant to investigate the various ways of enhancing individuals' willingness to invest in cooperative endeavors. We studied whether ascription of a transparent collective goal in a joint action promotes cooperation in a group.MethodsA total of 48 participants were assigned in teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…Although we have discussed some exceptions above [1315], it is noteworthy that the majority of studies that have demonstrated positive effects of synchrony were not outcome-oriented, but rather focused on interpersonal coordination as an end in itself [20,21]. When participating in more naturalistic tasks, people encounter considerably more coordination options permitting multiple means for achieving similar ends.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have discussed some exceptions above [1315], it is noteworthy that the majority of studies that have demonstrated positive effects of synchrony were not outcome-oriented, but rather focused on interpersonal coordination as an end in itself [20,21]. When participating in more naturalistic tasks, people encounter considerably more coordination options permitting multiple means for achieving similar ends.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the collective efficacy model suggested by Beauchamp (2007) affords a systematic view of different psychological processes, emphasizing that there are several antecedents, such as leadership, motivational climate, team cohesion, previous expectative, and past performance of group size, that influence players' perception of collective efficacy levels. Moreover, these levels of collective efficacy lead to behavioral consequences, emphasizing group performance (Leo, García-Calvo, Sánchez-Miguel, & Sánchez-Oliva, 2010;Mitkidis, Sørensen, Nielbo, Andersen, & Lienard, 2013;Myers, Payment, et al, 2004;Zaccaro et al, 1995). Taking into account this model, it seems that the coach's role, through his/her leadership and behaviors, have an influence on team members (Jowett & Chaundy, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As investigated by Pruitt and Kimmel, in order for people to effi ciently cooperate two conditions need to be satisfied: (1) a collective goal, and (2) expectations about the other's willingness to cooperate (Pruitt and Kimmel, 1977;Ariely, 2008;Mitkidis et al, 2013). In the goal-demoted condition, participants might not be able to coordinate their expectations with the oth ers' , since there was no obvious cooperative end-state to their contribution.…”
Section: Discussionmentioning
confidence: 99%